Numerical and experimental analyses for natural and non-natural impacted composites via thermographic inspection, ultrasonic C-scan and terahertz imaging; Proceedings of SPIE; Vol. 10214 : Thermosense: Thermal Infrared Applications XXXIX - Zhang H.; Sfarra S. Stefano; Genest M.; Sarasini F. Fabrizio; Perilli S.; Fernandes H. C. Henrique Coelho; Fleuret J. R. Julien; Maldague X. Xavier (2017, 2017)
Title screen